Eko Arsitektur Pada Kawasan Siliran LOR Tinjauan Pada Vegetasi - Prima Widia Wastuty (INFO-TEKNIK, 2007)
Eco architecture is the recently major issue especially related with global warming. Eco architecture has five element, they are land use, water treatment, vegetation, building, and transportation.Siliran Lor is one of the district in the inner part of the fort ofYogyakartapalace that make it has uniqe location, it also has good achievment as the winner of  the orderliness environment competition. The important reason why this area choosed as the research case is because it has leafy vegetation. Vegetation as one of the eco architecture’s element is the focus analysis in this research.  The result of this research hoped will give a good input in district planning and design that concern with the environment.The research in Siliran Lor indicate that it has variation in vegetation, with many functions and meanings. Some of the vegetations still have the simbolic meaning of they use, but most of them not.